Occurrence of juvenile fishes on the seagrass beds of Kavaratti Atoll, Lakshadweep, India - Vijayanand, P E; Pillai, N G K (Indian Journal of Fisheries, 2011)
In the atolls of Lakshadweep, juveniles of Acanthuridae and Labridae were most abundant on seagrass beds, the former during pre-monsoon and postmonsoon periods and the latter in pre-monsoon. Schooling species showed variable recruitment. Non-schooling species were rare. Peak settlement was observed during pre-monsoon and post-monsoon seasons. Continuous occurrence of juveniles in different size ranges confirms the continuous spawning habits. Chaetodontids and holocentrids occurred consistently round the year. Seasonality in occurrence was most pronounced in Carangidae and Siganidae, but not so in Apogonidae, Lutjanidae and Mullidae. Seasonal abundance of juveniles was influenced by summer peaks, timing and magnitude of settlement, adult spawning and local migrations. Abundance of larvae increased with salinity. Juvenile abundance, independent of environmental parameters seemed to be controlled by seasons, tides and currents. Lunar phases and abundance of juveniles were found to be co-related.